ANALISIS KEEFEKTIFAN KOMUNIKASI PADA BAGIAN UMUM PT X - Hanif, Muhammad Abdul; Wolor, Christian Wiradendi; Marsofiyati, Marsofiyati (Jurnal Riset Manajemen dan Akuntansi, 2023)
This research was conducted at the General Section of PT X when working employees interacted between one employee and another. Communication is also carried out by employees with superiors either verbally or non-verbally. Exchange of ideas or discussions is also carried out by employees as an exchange of communication to obtain clear information. For this reason, it is necessary to understand the effectiveness of communication and how good communication between employees and superiors is applied by the company. The findings that occur are new employees who do not understand the procedures and work systematics on their part. Communication is a mandatory condition for the creation of a social interaction. With the delivery of effective communication, it is also expected to be effective and minimize errors in work